A Case of severe mosquito bite allergy complicated by fatal hemophagocytic lymphohistiocytosis. Issue 3 (23rd March 2022) - Dupuy, Elizabeth; Afifi, Ladan; Jonas, Steven J.; Cheng, Carol E.; Hogeling, Marcia
Abstract: Severe mosquito bite allergy (SMBA) is characterized by necrotic skin lesions and systemic symptoms. Chronic active Epstein–Barr virus (EBV) infection, when superimposed with SMBA, is a key driver for catastrophic clinical consequences, such as uncontrolled lymphoproliferation. This interplay is of clinical significance due to its association with hemophagocytic lymphohistiocytosis (HLH) and/or EBV‐driven malignancies. Here, we report a case of SMBA that developed in a 14‐year‐old Hispanic boy that led to fatal secondary HLH.